Irrigation frequency and irrigation amount of micro-sprinkler irrigation mulched regulate N2O emission of tomato (Solanum lycopersicum) soil - Yang, Haijian; Zhang, Mingzhi; Wu, Wenqian; Xiao, Na; Sun, Mengmeng; Li, Yuan (Frontiers in Sustainable Food Systems, 2025)
IntroductionThere is a limited amount of research available on how changes in soil hydrothermal cycles impact soil N2O emissions in greenhouses that use a tomato irrigation system with micro-sprinkler irrigation mulched (MSM).MethodsThis study examined the effects of different irrigation frequency (F, F1 which is every 3 days, F2 which is every 5 days, F3 which is every 7 days) and irrigation amount (I, I1 which is 0.7 Epan, I2 which is 1.0 Epan, I3 which is 1.2 Epan) on soil N2O emissions in tomato cultivation. The research was carried out using a randomized experimental design over two consecutive growing seasons for greenhouse tomatoes in Northwest China.ResultsThe findings revealed that F1 and F3 did not support the accumulation of microbial biomass carbon and nitrogen in the tomato soil under MSM. This limitation hindered the enhancement of soil extracellular enzymes BG and LAP, and decreased the diversity of the bacterial community structure. The functional genes related to bacterial nitrogen metabolism were abundant. The application of I2 treatment can result in a high accumulation of microbial biomass carbon and nitrogen in tomato soil, leading to enhanced soil BG and LAP activities and contributing to the stability of the soil bacterial community structure. As the F decreased, the cumulative emission flux of N2O in tomato soil initially decreased, then increased. Increasing the I showed a rising trend in the cumulative emission flux of N2O in tomato soil. The yield of spring and autumn tomatoes in F2 was higher compared to F1 and F3 at approximately 5.27 and 3.24%, and 19.31 and 11.30%, respectively. The yield of spring and autumn tomatoes in I2 was around 24.44 and 26.15% higher than in I1 and 1.64 and 3.06% higher than in I3. The regulation of the irrigation system in MSM resulted in a favorable interaction among tomato soil, microbial biomass carbon and nitrogen, soil extracellular enzymes, and soil bacterial community. When the I increased by 1.00%, the cumulative N2O emission flux and yield of tomato soil increased by at least 30.68 and 39.24%, respectively. For every 1.00% increase in F, the cumulative N2O emission flux and yield of tomato soil decreased by at least 7.41% and 11.23%, respectively. A quadratic relationship was observed between soil N2O emission flux and the abundance and yield of soil bacterial nitrogen metabolism functional genes. The assessment of tomato yield potential in the area could be indirectly done by examining the abundance of soil bacterial nitrogen metabolism functional genes. The study demonstrates the feasibility of regulating soil N2O emissions under the MSM irrigation system. Moreover, the findings indicate that F2I2 can significantly improve tomato yield without causing a considerable rise in soil N2O emission flux.DiscussionThis conclusion can provide a scientific basis for the optimization of irrigation system in facility agriculture, so as to ensure the high yield of crops and reduce the negative impact on the environment. It is also of great significance for the green development of agriculture under the background of global climate change.